1982
DOI: 10.1177/000348948209100214
|View full text |Cite
|
Sign up to set email alerts
|

Semicircular Canal Structure during Postnatal Development in Cat and Guinea Pig

Abstract: The gain of the vestibulo-ocular reflex in the cat continues to increase for some time after birth. The reason for this increase is not presently known and one possibility if that it occurs because the cat semicircular canals increase in size. The present study examined this possibility by measuring the radii of curvature (R) of individual semicircular canals and the angular relationships of the semicircular canal planes within a labyrinth in cats and guinea pigs during postnatal growth. It was found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…During development, the whole labyrinth migrates from the base of the skull to its final position and orientation in the head (Bast and Anson 1949;Cox and Jeffery 2007;Curthoys et al 1982). As that The mean angle (± standard deviation) between each pair of canal planes from both left and right ears; calculated using the CrossSect weights The average plane equations for the six SCCs; calculated using the CrossSect weights and referenced to the RRSoC In each case, the orientation was chosen to best highlight the attribute being inspected.…”
Section: Bilateral Labyrinth Relationshipsmentioning
confidence: 99%
“…During development, the whole labyrinth migrates from the base of the skull to its final position and orientation in the head (Bast and Anson 1949;Cox and Jeffery 2007;Curthoys et al 1982). As that The mean angle (± standard deviation) between each pair of canal planes from both left and right ears; calculated using the CrossSect weights The average plane equations for the six SCCs; calculated using the CrossSect weights and referenced to the RRSoC In each case, the orientation was chosen to best highlight the attribute being inspected.…”
Section: Bilateral Labyrinth Relationshipsmentioning
confidence: 99%
“…Thus, the present findings demonstrate that functional maturation of the mouse vestibular function is delayed in relation to its anatomical maturation. Postnatal developmental changes in VOR responses have been reported in the rat and guinea pig, and these cannot be due to the increasing size of semicircular canals [Curthoys, 1979;Curthoys et al, 1982]. Therefore, functional maturation of the mouse vestibular system may reflect the development of central vestibular networks.…”
Section: Correlation Of Vor Responses With Abrsmentioning
confidence: 99%
“…The three rodent species examined so far (see Curthoys et al 1982;present paper) are the laboratory rat (with short gestation, altricial, rapidly growing young), the guinea-pig (long gestation, precocial, relatively rapidly growing young), and Cryptomys (long gestation, altricial, very slowly growing young). As stated above, it is only in the rat, and there only in the horizontal semicircular canal, that growth is observed for a short period after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Ten Kate (1970) has suggested that the increase of the vestibular organ in the fish guarantees constant sensitivity of the animal during its growth. However, the postnatal maturation of the vestibulo-ocular reflex in the cat indicates that even without dimensional changes there are still maturational changes in the receptor and neuronal levels (Curthoys et al 1982). Nothing is known about these maturational changes in Cryptomys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation